UPAYA KONTRATERORISME AMERIKA SERIKAT TERHADAP KELOMPOK TERORIS AL-QAEDA: STUDI KASUS KENYA TAHUN 1998 - Sari, Venisa Yunita; Rizky Fauzy, Ivan Sasiva; Artisa, Tasya; Febby, Stephanie Via (Majalah Ilmiah UNIKOM, 2020)
Terrorism is one of the actions that involve the security and sovereignty of all countries, including the United States. The bombing of the United States embassy in Kenya in 1998 has become one of the factors that makes the United States the next target for terrorism. Responding to this bombing action, the United States government under the leadership of Bill Clinton has managed to overcome this problem. This study discusses to analyze and describe the efforts of the United States government in dealing with Al-Qaeda terrorist groups during the Bill Clinton period. The methodology is descriptive qualitative, with data collection using secondary collection techniques through the previous research from books, scientific journals, newspapers, and website. While the theory is rational choice theory with concepts of counterterrorism. Based on the results of research and discussion of the efforts from the government in the United States government to overcome Al-Qaeda defense groups is a response, challenge, defense, and pursuit. Overall, the missile attacks from counterterrorism policies during Bill Clinton's time provided a change in the United States counterterrorism strategy to be more proactive and aggressive, more global, and oriented towards national security. Key Words : Al-Qaeda, Counterterrorism, Embassy Bombings, The United States of America